Pemanfaatan Solar Cell Sebagai Sumber Energi Alternatif Untuk Fasilitas Bangku Taman Ruang Terbuka Hijau - Kango, Riklan; Hadiyanto, Hadiyanto; Suhaedi, Suhaedi; Ihsan, Ihsan (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The source of electricity for the Taman Tiga Generasi facility, a Green Open Space in the City of Balikpapan, is highly dependent on PLN sources, resulting in an electrical energy crisis. Also, not all parks have facilities and infrastructure such as benches for visitors to sit on. Community service aims to apply electric bench technology with solar cell electricity generation for parks and implement Appropriate Technology products for the community based on solutions to partner problems. This community service method considers the health protocol in which the process is carried out directly and is limited. The stages are (1) Application of solar cell electricity technology to provide electricity for garden facilities; (2) Training by service team for partners regarding the operation and maintenance of electrical bench products with solar cell power supply; (3) Counseling regarding the conservation of electrical energy for partners. This community service resulted in a multifunctional electric bench product as a seat, as a place to charge mobile electronic devices, and as a source of lighting for the garden area with a solar panel-based power supply. Community service activities as part of the realization of alternative solar cells for electricity generation in Indonesia in saving electrical energy.